Organizacijsko učenje v policiji - Behlić, Edo (Teorija in praksa, 2020)
Organisations must develop and apply the process of organisational learning to cope with modern challenges. The cycle of organisational learning consists of the generation and acquisition of knowledge, its dissemination and its utilisation. When knowledge is transferred from the individual to the level of the organisation, the latter has greater opportunities for success. In the article, the concept of organisational knowledge and learning is applied to the Slovenian Police through the case of the transfer and use of the knowledge and experiences of police officers acquired in international civilian missions. Data were obtained with an opinion-based questionnaire with police peacekeepers and show that while on missions police officers obtain knowledge and experiences that are applicable to police work at home. They personally apply this knowledge in their own careers and education. They also transfer it to their fellow workers. However, the systematic transfer (dissemination) of this knowledge to the organisational knowledge of the Police is missing
Keywords: civilne misije; mednarodne misije; misije; Organizacijsko učenje; Organizational learning; Police; Policija; prenos znanja; Slovenska policija